Rabeprazole Combined with Hydrotalcite is Effective for Patients with Bile Reflux Gastritis after Cholecystectomy - Huimin Chen; Xiaobo Li; Zhizheng Ge; Yunjie Gao; Xiaoyu Chen; Yun Cui (Canadian Journal of Gastroenterology)
BACKGROUND: Regardless of surgical technique, patients who have undergone cholecystectomy appear to be predisposed to the development of bile reflux gastritis.